Experimental Study on Phytoremediation of Heavy Metal from Mine Wastewater by Rumex nepalensis Spreng.: Phytoremediation of heavy metal from mine wastewater - TECHANE, GERA; GEBRE, GEREMEW SAHILU; AMARE, ELFU (Borneo Journal of Resource Science and Technology, 2024)
Tailings pond is considered as the main source of heavy metal pollution in gold mining areas. These heavy metals are directly released into fresh water without proper treatment. Phytoremediation process with the selected terrestrial plants may be an alternative solution for the mine wastewater treatment. In the current study, an experimental investigation found that Rumex nepalensis Spreng. has found a good accumulator of multi-metals in 15 days of experimental period. The results revealed that the removal efficiencies for Zn, Cu, Ni and Pb were 100%, 92%, 87%, and 67%, respectively. These indicate the plant showed its maximum accumulation of multi-metals. However, Pb reached saturation at the end of the 10th day, which makes its removal efficiency only in the first 10 days of the experimental period. The experiment revealed Pb and Ni which were above WHO standard for drinking water in the mine wastewater were made to permissible limit for these metals after the treatment.